Radiofrequency Ablation as First-line Treatment of Varicose Veins. Issue 3 (March 2014) - Avery, John; Kumar, Keshav; Thakur, Vijaya; Thakur, Anjani
Endovascular radiofrequency ablation is a minimally invasive method to safely treat symptomatic refluxing varicose veins. A retrospective chart review was used to determine patient demographics, disease severity, treatment algorithm, and outcome in patients who underwent radiofrequency ablation of symptomatic refluxing veins that had failed conservative management. Statistical analysis was done using GraphPad Demo Version (San Diego, CA). Two hundred forty-one limbs in 179 patients (average age, 53 years; 73% females, 27% males) were treated. Preprocedure Clinical Etiological Anatomic and Pathologic (CEAP) scores were C2s: 236, C3s: 4, and C5s:1. Procedures were performed in the office using tumescent anesthetic; all patients could ambulate immediately after the procedure. Postprocedure total occlusion (TO) rate was seen in 93 per cent of limbs (223 limbs) at 3 months and 91 per cent of limbs (220 limbs) at 12 months posttreatment. No relationship was found between patients who did not have total occlusion and age, sex, diameter of veins, CEAP scores, preoperative reflux time, and volume of tumescent anesthetic ( P > 0.05). The VNUS procedure is an in-office, minimally invasive procedure with a low complication rate and quick recovery. Total occlusion rates are high and there is improvement in disease severity after treatment.